Strategi Pondok Pesantren dalam Meningkatkan Kedisiplinan Santri: Studi Deskriptif di Pondok Pesantren Perkampungan Minangkabau - Risman, Desy Fitri; Saputra, Edi (TSAQOFAH, 2025)
Student discipline is a key factor in the success of education and character development in pesantren; however, violations disrupting order still frequently occur. This study aims to identify the strategies implemented at Pondok Pesantren Perkampungan Minangkabau to improve student discipline. A descriptive qualitative method was employed, involving observation, interviews, and document collection from the pesantren administrators, kyai, and students. The findings reveal that the pesantren applies the IQOB strategy, a form of punishment or penalty functioning as a means of self-evaluation and self-improvement, thereby fostering the growth of independent, disciplined, ethical, and responsible individuals. These findings provide a concrete depiction of disciplinary challenges in pesantren and demonstrate the effectiveness of the IQOB strategy in creating a more conducive learning environment. The study also opens opportunities for further research on unresolved issues related to discipline.